Crises Management as Strategic Coping - Klausen, Kurt Klaudi (Scandinavian Journal of Public Administration, 2024)
To which extent bureaucracies are inflexible and strategic planning is incompatible with emerging coping strategies are empirical questions. Based on a longitudinal case study of neo-Weberian state type local governments responses to different types of crises, this article argues that bureaucracies are at the heart of local coping strategies and indeed capable of adjusting to changing environments. They demonstrate capacious variation. The study adds the strategic perspective, falsifies the theoretical claims of the New Public Government (NPG) and confirms the ones of the neo- Weberian state (NWS). Strategic planning is far from dead. Crisis management was left to the CEOs and the administrative system, and it was top-down driven. Strategic plans had a life alongside strategic manoeuvring, and a variety in the hybrid mix of governance paradigms - as well as clear patterns of isomorphic structures - are interpreted as functional and symbolic adjustments.